Sosialisasi Teknik Penyusunan Artikel dan Publikasi Ilmiah dalam Penelitian Bidang RMIK - lestari, tri; Hastuti, Nunik Maya; Rohmadi, Rohmadi (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2024)
A scientific article is a factual or non-fiction essay about a problem published in a journal, magazine or bulletin with the aim of conveying ideas and facts, in order to convince, educate and offer a solution to a problem. (Komara, 2017). Based on the initial interview results, it is known that all PMIK have an obligation to fulfill 3 domains in the STR extension process which can be obtained from Domain D (Scientific Development-Research in the RMIK Sector which has been published in ISSN media and scientific publications) and Domain E (Scientific Publications -Write scientific papers for publication), where PMIK can get SKP if they carry out research in the RMIK field which is compiled into a scientific article and has been published in ISSN or ISBN media. Apart from that, there are still minimal scientific publications carried out by PMIK professionals, Based on a preliminary survey, 90% of PMIK felt difficulties in preparing scientific articles and did not understand how to carry out scientific publications. The aim of this community service is to identify PMIK's level of understanding of the fulfillment of 3 (three) domains of SIPORLIN (CPD Nakes) in the STR Extension Process, Identifying the level of understanding of how to prepare scientific articles in research in the RMIK field at PMIK and knowing the level of motivation to conduct research and publish scientific articles in the field of RMIK. Method: Delivery of socialization material and Focus Group Discussion (FGD. The results are for PMIK's level of understanding regarding the fulfillment of domain 3, Level of understanding of how to prepare scientific articles in RMIK research, The overall level of motivation to conduct research and publish scientific articles in the field of RMIK has increased. Conclusions can be drawn from 18 research titles in the RMIK field that are ready to be submitted by PMIK at RSUD Ir. Soekarno Sukoharjo